KOMPARASI TINGKAT KESEHATAN BANK ANTARA BANK KONVENSIONAL DAN BANK DIGITAL BERDASARKAN METODE RGEC - Saputra, Septian Rahul Dika; Tarigan, Thia Margaretha; Prasetyo, Christianus Yudi; Setiabudi, Andang Wirawan (Universitas Katolik Indonesia Atma Jaya, 2024)
The research aims to compare the soundness level of banks between conventional banks and digital banks that have been listed on the Indonesia Stock Exchange in 2020 and 2021 using the Risk Profile, Good Corporate Governance, Earning, Capital and RGEC methods. The research was conducted using a descriptive research type with the use of secondary data originating from the website www.idx.com and annual reports issued by banking companies officially to support the research. The sample was done using the purposive sampling technique. The data analysis technique used is the Risk-based Bank Rating method. The results of the study show that conventional banks will be healthier than digital banks in 2020 and 2021 based on 4 assessment aspects, namely: Good Corporate Governance, Earning, Capital, and RGEC methods. Meanwhile, based on the Risk Profile factor, in 2020 and 2021, conventional banks and digital banks will have the same level of soundness.